Leptosphaeria maculans Alters Glucosinolate Profiles in Blackleg Disease–Resistant and -Susceptible Cabbage Lines - Robin, Arif Hasan Khan; Yi, Go-Eun; Laila, Rawnak; Hossain, Mohammad Rashed; Park, Jong-In; Kim, Hye R.; Nou, Ill-Sup (Frontiers in Plant Science, 2017)
Blackleg, a fungal disease caused by Leptosphaeria maculans, is one of the most devastating diseases of Brassica crops worldwide. Despite notable progress elucidating the roles of glucosinolates in pathogen defense, the complex interaction between B. oleracea (cabbage) and Leptosphaeria maculans infection that leads to the selective induction of genes involved in glucosinolate production and subsequent modulation of glucosinolate profiles remains to be fully understood. The current study was designed to identify glucosinolate-biosynthesis genes induced by L. maculans and any associated alterations in glucosinolate profiles to explore their roles in blackleg resistance in 3-month-old cabbage plants. The defense responses of four cabbage lines, two resistant and two susceptible, were investigated using two L. maculans isolates, 03-02s and 00-100s. A simultaneous increase in the aliphatic glucosinolates glucoiberverin (GIV) and glucoerucin (GER) and the indolic glucosinolates glucobrassicin (GBS) and neoglucobrassicin (NGBS) was associated with complete resistance. An increase in either aliphatic (GIV) or indolic (GBS and MGBS) glucosinolates was associated with moderate resistance. Indolic glucobrassicin (GBS) and neoglucobrassicin (NGBS) were increased in both resistant and susceptible interactions. Pearson correlation showed position association between GER content with GSL-OH (Bol033373) expression. Expressions of MYB34 (Bol007760), ST5a (Bol026200) and CYP81F2 (Bol026044) were positively correlated with the contents of both GBS and MGBS. Our results confirm that L. maculans infection induces glucosinolate-biosynthesis genes in cabbage, with concomitant changes in individual glucosinolate contents. In resistant lines, both aliphatic and indolic glucosinolates are associated with resistance, with aliphatic GIV and GER and indolic MGBS glucosinolates particularly important. The association between the genes, the corresponding glucosinolates, and plant resistance broaden our molecular understanding of glucosinolate mediated defense against L. maculans in cabbage.